A Comparison between primary and secondary wound closure after surgical removal of lower third molars according to pain and swelling (Mustansiria Dental Journal, 2018)
The aim of this study was to compare between Primary and secondary closure techniques after removal of impacted third molars. This comparison was carried out according to the pain and swelling parameter. One hundred patients with impacted third molars were randomly divided into two groups (50 patients in each group). Periapical radiographs were taken for each patient to determine the degree of eruption and angulations of third molars. After surgical extraction in Group I, the socket was closed by hermetical suturing of the flap while in Group II; a 5–6 mm wedge of mucosa adjacent to the second molar was removed to obtain secondary healing. Swelling and pain were evaluated for 7 days after surgery with the VAS scale. The statistical analysis (analysis of variance for repeated measures, P < 0.05) showed that pain was greater in GI, although it decreased over time similarly in the two groups (P=0.003, F=2.6613). Swelling was significantly worse in Group I (P < 0.0001, F=38.395). In Group I, dehiscence of the mucosa was present in 15% of patients at day 7, and 1% showed signs of re-infection with suppurative alveolitis at 30 days. Pain and swelling were less severe with secondary healing than with primary healing.